Generation of Phase-Only Fourier Hologram Based on Double Phase Method and Quantization Error Analysis - Yang Wu; Jun Wang; Chun Chen; Chan-Juan Liu; Feng-Ming Jin; Yu-Hen Hu (IEEE Photonics Journal)
The double phase method is an efficient way to generate phase-only holograms with high reconstruction quality due to no addition of a random phase. However, it cannot directly encode the Fourier spectrum because of the limited gray modulation range of spatial light modulator, and quantization error. This shortage restricts the application of the double phase in the phase-only Fourier hologram, and this issue is never discussed, and solved as far as we know. To solve this issue, we propose a method to generate phase-only Fourier hologram by analyzing quantization error, and adding a proper quadratic phase. The proposed method overcomes the shortage, and outperforms the non-iterative bidirectional error diffusion method in reconstruction quality, and calculation speed with 8.9 dB higher, and 33 times faster on average, respectively.